Comovements of ethanol‐related prices: evidence from Brazil and the USA. Issue 2 (8th June 2015) - Kristoufek, Ladislav; Janda, Karel; Zilberman, David
Abstract: We use the wavelet coherence methodology to investigate the relations between prices of ethanol and its feedstocks. Our continuous wavelet framework allows for discovering price connections and their evolution in both time and frequency domain in the most important ethanol markets – Brazil and the USA. For both of these markets, we show that the long‐run relationship between prices of ethanol and corn (in the USA) or sugar (in Brazil) is positive, strong and stable in time. Importantly, we show that the prices of feedstock lead the prices of ethanol and not the other way around. The price lead of feedstock is documented for both short‐ and long‐run horizons. Our qualitative results hold true even when the influence of crude oil prices is accounted for by utilizing partial wavelet coherence approach.